(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This paper investigates the optimization of thermal conductivity in sustainable aluminum nitride (AlN)–fly ash based composite materials aimed at eco-friendly thermal management applications. Fly ash, an industrial waste by-product, is incorporated to enhance sustainability and reduce material cost, while AlN is used to improve heat conduction due to its high intrinsic thermal conductivity. Composite samples were fabricated with varying AlN and fly ash compositions, and their thermal conductivity was experimentally evaluated using standard measurement techniques. The influence of material composition and microstructural characteristics, including particle dispersion, interfacial bonding, and porosity, on thermal performance was systematically analyzed. An optimization strategy was employed to determine the optimal reinforcement ratio that achieves a balance between enhanced thermal conductivity and environmental sustainability. The results indicate that increasing AlN content significantly improves thermal conductivity, while the presence of fly ash maintains eco-efficiency with acceptable performance trade-offs. The optimized composite demonstrates superior thermal behavior compared to conventional sustainable composites, highlighting its potential for applications in electronics cooling, energy systems, and environmentally conscious construction materials.